Implementation of Dry Port: Feasibility Study in Jeneponto Regency - Amrin Amrin; M. Azhar Shauqy; Sri Nur Aulia (Program Pascasarjana Universitas Negeri Makassar, 2023)
This research was conducted to analyze the feasibility of Jeneponto Regency as a location for a Dry Port in South Sulawesi and the impact it has on the selection of the Dry Port location. This research used a qualitative descriptive method and SWOT analysis aimed at analyzing data such as geographic data, supporting infrastructure, economic and social aspects, regional characteristics, and local government policies regarding regional development. In addition, field surveys and interviews were conducted with relevant parties, including government agencies, private institutions, academics or practitioners, and other stakeholders. The results of this research indicate that Jeneponto Regency has the potential to be a strategic location for a Dry Port, with a recorded area of 749.79 km2. The planning for the development of the Jeneponto Regency Dry Port is located in the Bontorappo Village area, Tarowang District, with an available land area of 1.85 hectares. This region has good accessibility through the main road network and is close to the Port of Makassar, one of the busiest ports in South Sulawesi. Furthermore, the potential for economic and industrial growth in this regency also provides promising opportunities for Dry Port development. The related impacts on the selection of the Dry Port location are assessed in terms of economic impact, impact on the smooth flow of cargo handling, and impact on regional development. The SWOT analysis results indicate that the positioning falls within quadrant I, which means that the development strategy of the Dry Port in Jeneponto Regency, South Sulawesi Province, supports an aggressive growth-oriented strategy. This situation is highly advantageous for the policies to be implemented, where the strength of the strategic location for Dry Port development positively impacts the efficiency and speed of goods delivery, and the opportunities for Dry Port development will create new job opportunities and have significant economic benefits for the local area. Therefore, based on the positioning in quadrant I, the Dry Port project in Jeneponto Regency has a high potential for rapid growth.